Efficient removal of hexavalent chromium from water by Bacillus sp. Y2-7 with production of extracellular polymeric substances - Wang, Xuehan (Environmental technology, 2024)
Bioremediation is an environmentally friendly technology for the treatment of chromium-contaminated sites. Here, a hexavalent chromium [Cr(VI)]-resistant strain was isolated from oil-contaminated soil and designated as Bacillus sp. Y2-7 based on 16S rDNA sequence characterization. The effects of various factors including inoculation dose, pH value, glucose concentration, and temperature on Cr(VI) removal rates were then evaluated. Based on the response surface methodology, optimal Cr(VI) removal efficiency (above 90%) could be achieved at an initial Cr(VI) concentration of 155.0 mg·L-1, glucose concentration of 11.479 g·L-1, and pH of 7.1. The potential removal mechanisms of Cr(VI) by strain Y2-7 were also supposed. The contents of polysaccharide and protein in extracellular polymer (EPS) of strain Y2-7 decreased slowly after cultured with Cr(VI) of 15 mg·L-1 from 1 to 7 days. We thus inferred that EPS bonded with Cr(VI) and underwent morphological changes in water. Molecular operating environment (MOE) analysis suggested that macromolecular protein complexes in Bacillus sp. Y2-7 and hexavalent chromium could establish hydrogen bonds. Collectively, our findings indicate that Bacillus sp. Y2-7 is an excellent bacterial candidate for chromium bioremediation